The investigation of aflatoxin, ochratoxin a and zearalenone residues in feeds and feedstuffs by chromatographic method - H. Ahmet ACET; Ömer DEMET; Bünyamin TRAŞ (Eurasian Journal of Veterinary Sciences)
This investigation was conducted to determine the levels of aflatoxins, ochr'atoxin A and zearalenone in feeds and feedstuffs obtained from various regions of Turkey.